Economic policy in postwar Japan : growth versus economic democracy - Yamamura, Kōzō (Publications of the Center for Japanese and Korean Studies., 2022)
Since the end of the Pacific War, Japan has, broadly speaking, pursued two economic policies: a ""democratization"" policy laid down by the Allied Powers, and subsequently a ""de-democratization"" policy formulated and vigorously pursued by the independent government. Yamamura here addresses himself to two central questions: What were the objectives and results of each policy? And why and how did the earlier one give way to the later? Yamamura never loses sigh.